"I Have Removed My Ceiling": Qualitative Experiences of Teachers on Their Professional Development. (June 2022) - Garces-Bacsal, Rhoda Myra; Elhoweris, Hala; Mohamed, Ahmed; Almuhairy, Osha; Safi, Mohammad; Moustafa, Ashraf; Alzyoudi, Mohammed
Gifted education in the United Arab Emirates is a nascent field that is coming into greater visibility with corresponding governmental and institutional support over the past 15 years. Massive efforts are now being strategically put in place, which includes actively training teachers to meet the government's aim to prioritize giftedness and innovation at all levels and sectors, so that classroom pedagogies align with said initiatives to support gifted students. However, there is limited information about how teachers perceive the efficacy of the training they have received. This research aims to highlight the voices of teachers who received professional development on teaching the gifted over a 2-year period. Research findings revealed how teachers conceptualized "innovation" in their own teaching practice with the gifted, the participants' perceptions on program impact, and the challenges faced in implementing what they have learned in their professional development.